RETRACTED : Analysis of the Ratio of Growth, Effectiveness and Budget Efficiency at the Ministry of Religious Affairs of the Republic of Indonesia in 2017 – 2022 - Romidi Karnawan; Agus Siswanto; Kumba Digdowiseiso (Journal of Social Science, 2024)
A budget is a written plan regarding the activities of an organization which is expressed quantitatively for a certain period or period and is generally expressed in units of money. The Ministry of Religion of the Republic of Indonesia is one of the ministries that has authority over the State revenue and expenditure budget. The Ministry of Religion is ranked 2nd with the largest APBN ceiling after the Police of the Republic of Indonesia. The ratios for assessing financial performance in the Ministry of Religion used in this research include: Growth Ratio, Effectiveness and Efficiency Ratio. This research aims to analyze the level of Growth, Effectiveness and Efficiency Ratios during the 2017-2022 period to see the financial performance of the Ministry of Religion of the Republic of Indonesia. In writing this journal, a quantitative descriptive analysis method was used. The results of this research show that the financial performance of the Ministry of Religion using the Growth Ratio or the Ministry of Religion's budget growth ratio is around 4.39% every year. The Ministry of Religion's budget effectiveness ratio is relatively high at an average level of 112%, which means that budget realization is able to exceed the set targets. The highest achievement of 121% was recorded in 2017. The Ministry of Religion's budget efficiency ratio for 2017-2022 is at an average of 0.97%, which is very efficient considering the nature of the public sector budget, the smaller the efficiency ratio, the better the government's performance.